CFD evaluation of building geometry modifications to reduce pedestrian-level wind speed. (October 2019) - van Druenen, T.; van Hooff, T.; Montazeri, H.; Blocken, B.
Abstract: High-rise buildings can significantly increase the wind speed at pedestrian level, and knowledge of building aerodynamics and pedestrian-level wind (PLW) conditions is therefore imperative in their design. This study aims at evaluating different building geometry modifications to reduce PLW speed around an isolated high-rise building. Numerical simulations with computational fluid dynamics (CFD) are performed to evaluate the effect of canopies, podiums and permeable floors. To the best knowledge of the authors, a systematic study on the impact of these modifications on PLW conditions using validated CFD simulations has not been reported before. Grid-sensitivity analyses are performed and sub-configuration validation is applied using wind-tunnel measurements from the literature. It is shown that a canopy or a podium can significantly reduce the area-averaged PLW speed (up to 29%) and maximum PLW speed (up to 36%) around the high-rise building. In general, the PLW speeds decrease with increasing canopy or podium size. The introduction of a permeable floor to the building can reduce the maximum and area-averaged mean wind speed. However, when low-floor building layers are removed, adverse effects are noted, i.e. the average PLW speed increases (up to 21%) and the lower-speed wake region behind the building is reduced in size. Graphical abstract: Image 1 Highlights: A systematic parametric CFD study on reducing pedestrian-level wind speeds. Canopies, podiums and permeable floors in various configurations are evaluated. Mean wind speeds decrease with increasing canopy or podium size. Permeable floors at mid-lower heights can decrease the maximum mean wind speeds. Smaller podia and permeable floors at low heights can increase mean wind speeds.